Elemental Tracing of Original with Plastic Pearl by Atomic Emission Spectra - Muhammad Sufi; Abdul Rahman, Misbahul Muneer; Rosley, Rozainita; Ali, Ahmad Hadi; Haider, Syed Zuhaib (Multidisciplinary Applied Research and Innovation, 2020)
Pearls continued to be used luxuriously, and their lavish use is best reflected in the famous mosaic picture. The production of imitating pearl makes user muddled by too much same-looking items.  Fast and reliable technique is demanded to distinguish between imitate and original ones. The objective of this study is being able to differentiate between natural pearl and plastic pearl using laser ablation technique. High energy Nd:YAG laser pulse was focused on those samples and evaporise samples in form of plasma plume. Upon deexcitation of the excited electron, electromagnetic radiation which was not being absorbed by the plasma itself was emitted throughout the space and create small crater on samples. The light emission from the plasma was collected through spectrometer and analyzed carefully. The elemental mapping was being carried by matching the central peak of emission lines with standard one. Plotting of optical emission spectrum recorded easily distinguish between original and imitate ones. Moreover, elemental tracing showing existence of few elements which is not available in the plastic pearl includings Fe, Sn, Mn, Si, Hg, Mg, and Ba. The study implies optical emission spectroscopy as fast technique to differentiate original and imitate organogenic gems. In future, quantification technique could be applied to identify quantity of dissolving elements in this fascinating gems